PENERAPAN PENDEKATAN INVESTIGASI DALAM PROSES PEMBELAJARAN MATEMATIKA SISWA KELAS XI IPS SMA NEGERI 12 PADANG - Rahmi, Rahmi; Fauza, Hilmi Sufafri (Prodi Pendidikan Matematika, 2013)
The infortance of mathematicsâ role indicates that the students have to learn mathematics seriously, and actively. So, they are able to understand the concept of math, reasoning and communication, and problem solving. The reasearcher found that students of class XI Social department SMAN 12 padang dit not understand concept of math well. It could be seen from the degree of completeness of mid semester 2008-2009 academic year, taht was only 53%.One of learning model that was applied to overcome this problem was cooperative learning type Group Investigation (GI). Investigation is a learning activity which gives a chance to students to improve their understanding through several activities and the result will be suitable with the studentsâ development. The research Questions of this study were: 1) How were the activities of the student class XI Social department SMAN 12 Padang through Group Investigation (GI) approach?, 2) How were the result of learning of students class XI Social department SMAN 12 Padang applying Group Investigation?This study was pra experiment, it was One-short case study design, in which this research was done only on one group without having control group.Based on data analysis, it could be concluded that generally studentsâ activity tend to icrease. Based on post-test, it was gotten that the mean score of the result of math learning was 68.18 in which the percentage of completeness was 82.05%